Rabi oscillations of X-ray radiation between two nuclear ensembles. Issue 11 (November 2017) - Haber, Johann; Kong, Xiangjin; Strohm, Cornelius; Willing, Svenja; Gollwitzer, Jakob; Bocklage, Lars; Rüffer, Rudolf; Pálffy, Adriana; Röhlsberger, Ralf
Abstract The realization of the strong coupling regime between a single cavity mode and an electromagnetic resonance is a centrepiece of quantum optics. In this regime, the reversible exchange of a photon between the two components of the system leads to so-called Rabi oscillations. Strong coupling is used in the optical and infrared regimes, for instance, to produce non-classical states of light, enhance optical nonlinearities and control quantum states. Here, we report the first observation of Rabi oscillations of an X-ray photon between two resonant57 Fe layers embedded in two coupled cavities. The system is described by an effective Hamiltonian, in which the two layers couple strongly. We observe sinusoidal beating as the signature of the Rabi oscillations in the system's temporal evolution, as well as the splitting of nuclear resonances in the reflected light spectrum. Our results significantly advance the development of the new field of X-ray quantum optics. Rabi oscillations in the regime of hard X-rays are observed between two ensembles of the nuclear resonant isotope57 Fe. The sample system consists of two thin-film cavities stacked on top of each other, coupled through a thin interlayer.